2014
DOI: 10.1155/2014/832723
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Severity Prediction of Traffic Crash on the Curve

Abstract: With the study of traffic crashes on curved road segments as the focus of research, a logistic regression based curve road crash severity prediction model was established based on a sample crash database of 20000 entries collected from 4 regions of China and 15 evaluation indicators involving driver, driving environment, and traffic environment factors. Maximum Likelihood Estimation and step-back technique were deployed for data analysis, the conclusion of which is that the three main contributory factors on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Considering the severity of the crash to be a dichotomous dependent variable, x1, x2, …xp are its corresponding independent variables, logit model may be established as; [20].…”
Section: Logistic Regression Analysismentioning
confidence: 99%
“…Considering the severity of the crash to be a dichotomous dependent variable, x1, x2, …xp are its corresponding independent variables, logit model may be established as; [20].…”
Section: Logistic Regression Analysismentioning
confidence: 99%
“…Apart from that, slippery road has been reported to lead the accident causation especially in US and several other countries like Finland, Malaysia and Iran [10,[12][13][14][15][16]. Moreover, three studies conducted in China and a study conducted in Malaysia reported that asphalt-paved road with smoother surface is also prone to cause road accident [17][18][19][20]. The accident severity can become even worst when driving on the wet, slippery and smoother road surface especially when the tires tread wear.…”
Section: Road Faultymentioning
confidence: 99%
“…The situation is worsening for the motorcyclists since riding on uneven road can cause them to loss balance and fall from their motorcycles [15]. Finally, other road surface qualities such as dry and frictional surface can also significantly lead towards accident [18,22,23].…”
Section: Road Faultymentioning
confidence: 99%
“…Frequently used techniques are: 1) logistic regression, 2) multinomial logit or nested logit model also known as unordered Siddique 149 response model and 3) ordered response model widely known as ordered probit or logit model. Xi et al (2014) studied the influence of road geometric element (at curve segment) on road crash severit, using logistic regression model. The investigation analyses the accident data based on 15 evaluation indicator including driver, driving conditions and traffic factors.…”
Section: Literature Reviewmentioning
confidence: 99%